2018
DOI: 10.1002/chem.201800775
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Approaches to Tetracyclic Indolines as Versatile Building Blocks of Diverse Indole Alkaloids

Abstract: Indole alkaloids bearing the tetracyclic indoline scaffolds of 1H-pyrrolo[2,3-d]carbazole have shown fascinating chemical diversity and significant biological activities. The development of efficient synthetic methodologies for such a tetracyclic scaffold remains highly desirable in both synthetic chemistry and medicinal chemistry. This review outlines key strategies for the construction of the tetracyclic indoline scaffolds in total syntheses of many indole alkaloids. The key strategies include nucleophilic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(34 citation statements)
references
References 161 publications
(110 reference statements)
0
34
0
Order By: Relevance
“…1 Ethyl cis-3-(9-allyl-2,3,4,4a,9,9a-hexahydro-1H-carbazol-4a-yl)propanoate (10g). According to GPB, δ-oxoester 9a (117 mg, 590 μmol) and 1-allyl-1-phenylhydrazine [20] (105 mg, 708 μmol) were converted with NaBH(OAc) 3 -3-(5a,6,7,8,9,10-hexahydro-5H-cyclohepta[b]indol-10ayl)propanoate (10h). A solution of δ-oxoester 9b (213 mg, 1.00 mmol) and phenylhydrazine (162 mg, 1.50 mmol) in glacial acetic acid (2 mL) was stirred at 100°C for 5 h and subsequently cooled to ambient temperature.…”
Section: Ethyl Cis-3-(2344a99a-hexahydro-1h-carbazol-4a-yl)propamentioning
confidence: 99%
See 1 more Smart Citation
“…1 Ethyl cis-3-(9-allyl-2,3,4,4a,9,9a-hexahydro-1H-carbazol-4a-yl)propanoate (10g). According to GPB, δ-oxoester 9a (117 mg, 590 μmol) and 1-allyl-1-phenylhydrazine [20] (105 mg, 708 μmol) were converted with NaBH(OAc) 3 -3-(5a,6,7,8,9,10-hexahydro-5H-cyclohepta[b]indol-10ayl)propanoate (10h). A solution of δ-oxoester 9b (213 mg, 1.00 mmol) and phenylhydrazine (162 mg, 1.50 mmol) in glacial acetic acid (2 mL) was stirred at 100°C for 5 h and subsequently cooled to ambient temperature.…”
Section: Ethyl Cis-3-(2344a99a-hexahydro-1h-carbazol-4a-yl)propamentioning
confidence: 99%
“…[10] Oxoester 5 was con-verted with phenylhydrazine under acidic conditions in the presence of Et 3 SiH as reducing agent furnishing the racemic hexahydrocarbazole derivative 6 exclusively as the diastereoisomer with cis-annulated rings. After formation of the hydrazone and its tautomeric enamine 7, the reaction proceeded along the known mechanistic pathway: protonation at nitrogen, [3,3]-sigmatropic rearrangement, nucleophilic addition of the aniline-NH 2 to the iminium ion at the alicyclic ring followed by elimination of ammonia furnishing the iminium ion 8. Instead of being deprotonated (since R ≠ H) forming the aromatic tetrahydrocarbazole, the cation 8 was reduced by the silane forming the hexahydrocarbazole derivative 6.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of the 1,5-methanoazocino [4,3-b]indole structure in another type of alkaloids has also led further progress of paths to this frame, which could be an advantageous exemplary for the access to key infrastructure and analogues of Strychnos alkaloids (Figure 1) [9,10]. These alkaloids constitute a key subgroup of the Strychnos alkaloids [11][12][13][14][15][16][17][18][19][20] and belong to moneterpenoid indole alkaloids, which are represented by the existence of the 1,5-methanoazocino [4,3-b] indole, including the tetracyclic ring system. Our aim to synthesize deethyltubifolidine is predicated on the structure of a 1,5-methanoazocino [4,3-b] indole skeleton, the basic component of deethyltubifolidine and other type alkaloids, by recognizing tetrahydrocarbazole analogues transporting a monoalkyl nitrile side chain (1) with tetrachloro-1,4benzoquinone (TCB) [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…1 Indoline derivatives are a very important class of heterocyclic compounds due to their presence as core structures in many naturally occurring alkaloids and pharmaceutical compounds. 2 In pioneering work, Chapman and co-workers 3 demonstrated that N -alkyl- N -aryl-enamines produce upon irradiation mainly trans -fused hexahydrocarbazoles, while Schultz et al 4 reported the formation of cis -fused dihydrobenzofurans from β-aryloxyenones via photochemical conrotatory ring closure followed by epimerization. These and other reports proved the efficiency of a [6π] photocyclization reaction in the generation of complex carbo- and heterocycles from simple starting materials.…”
Section: Introductionmentioning
confidence: 99%